PENGARUH LINGKUNGAN KELUARGA, FASILITAS, BELAJAR, DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR PRESTASI BELAJAR SISWA KELAS XI PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN LEMBAGA SMK NEGERI JAKARTA PUSAT - Amarudin Syahrul Ramadhan; Santi Susanti,S.Pd., M.Ak; Dr.Achmad Fauzi,S.Pd., M.Ak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the effect of the family environment, learning facilities, and learning interest on students’ achievement in the subject of Accounting Practicum for Services, Trade, and Manufacturing at SMK Negeri Jakarta Pusat. The study employed a quantitative approach with data collected through questionnaires and documentation. The target population consisted of 213 students in the 11th grade of the Accounting and Financial Institution Program. The sampling method used was simple random sampling. The analysis revealed that: (1) the family environment significantly influences student achievement, (2) learning facilities have a significant impact on student achievement, (3) interest in learning positively affects student achievement, and (4) collectively, these three factors family environment, learning facilities, and learning interest have a significant simultaneous effect on student achievement in the Accounting Practicum subject. These findings have practical implications for various parties, including: parents are expected to create a home environment that supports the learning process; schools need to provide comfortable and well-equipped classrooms; students are encouraged to be more active and enthusiastic in learning; and teachers need to adapt their teaching methods to students' learning styles and provide adequate emotional support.